The one and only Ivan [compact disc, unabridged] - Applegate, Katherine (HarperAudio, 2013)
Ivan is an easygoing gorilla. Living at the Exit 8 Big Top Mall and Video Arcade, he has grown accustomed to humans watching him through the glass walls of his domain. He rarely misses his life in the jungle. In fact, he hardly ever thinks about it at all. Then he meets Ruby, a baby elephant taken from her family, and she makes Ivan see their home-and his own art-through new eyes. When Ruby arrives, change comes with her, and it's up to Ivan to make it a change for the better.